2005
DOI: 10.1242/jeb.01755
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of high-pass filtering in zebrafish larval muscle fibres

Abstract: SUMMARY Larval somatic muscle of the zebrafish, Danio rerio, like that of some other organisms, responds to a sustained depolarization with one, and only one, action potential. Here, we report computer simulations, using the NEURON simulation programme, of sodium and potassium currents of somatic muscle of larval Danio rerio to investigate their possible contribution to once-only firing. Our computer model incorporated simulated sodium and potassium ion channels based on steady-state and kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…1a(ii); V 0.5 activation simulated = 11.5 mV, slope = 9.2; V 0.5 activation measured = 4.7 mV, slope = 12; from Kidd et al 2006). The depolarizing shift in the voltage dependence of activation and the reduced slope of the Boltzmann equation had also been observed in a similar study (Buckingham and Ali 2005). We found that improvements could be made in the voltage dependence of activation by speeding activation and slowing inactivation.…”
Section: Modeling Of Currents Under Voltage Clampsupporting
confidence: 85%
See 1 more Smart Citation
“…1a(ii); V 0.5 activation simulated = 11.5 mV, slope = 9.2; V 0.5 activation measured = 4.7 mV, slope = 12; from Kidd et al 2006). The depolarizing shift in the voltage dependence of activation and the reduced slope of the Boltzmann equation had also been observed in a similar study (Buckingham and Ali 2005). We found that improvements could be made in the voltage dependence of activation by speeding activation and slowing inactivation.…”
Section: Modeling Of Currents Under Voltage Clampsupporting
confidence: 85%
“…1a(iii, iv); V 0.5 inactivation simulated = -56.1 mV, slope = 7.3). Following Buckingham and Ali (2005), this suggests that the simulated channels faithfully reproduce voltage-clamp experimental data. Figure 1b(i) shows the simulated delayed rectifier K + currents (Kdr) obtained in response to 50 ms depolarizing steps from -80 to 60 mV in 10 mV increments.…”
Section: Modeling Of Currents Under Voltage Clampmentioning
confidence: 70%
“…Aside from their anatomical differences, these muscle types are physiologically distinct, with different electrophysiological phenotypes (Buss and Drapeau, ; Buckingham and Ali, ; Coutts et al, ) and functional roles (Buss and Drapeau, ), and arise from different precursor cells (Devoto et al, ). Red fibers do not express voltage gated Na + channels and do not support action potentials (Buckingham and Ali, ; Buckingham and Ali, ), thus they possess some of the hallmarks of tonic fibers. In addition, the red and white fibers are differentially innervated by motor neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In neurones the A‐type current also plays a role in affecting the frequency of action potentials (Connor & Stevens 1971, Rudy 1988, Tierney & Harris‐Warrick 1992). However, the fact that zebrafish muscle fibres only fire once, even in the presence of sustained excitatory input (Buckingham & Ali 2004, 2005, Coutts et al. 2006), suggests that modulation of the A‐type current in this preparation may have little effect on the frequency of firing.…”
Section: Discussionmentioning
confidence: 97%